Exploring the Potential for Sustainability Innovations (Ökologisches Wirtschaften - Fachzeitschrift, 2016)
Sustainable supply chain management can drive sustainability. The interpretation of Sustainable supply chain management as an upstreamoriented strategy has an important, but limited potential. Addressing consumer needs and lifestyles downstream can increase the sustainability potentials of Sustainable supply chain management.